Efeito da adição de zeína e colágeno hidrolisado nas características físicas de pão sem glúten - Costa, Raíssa Ingrid Santana Araújo (2021)
Bread with good quality characteristics requires adequate performance in relation to the development of dough and physical aspect of bread. Therefore, the need to study the technological characteristics of gluten substitutes was presented, especially for breads, such as the use of gluten-free flours, such as rice flour, and the addition of proteins in the dough, such as zein and hydrolyzed collagen. The present work aimed to develop gluten-free breads made with rice flour, with the addition of zein and hydrolyzed collagen in different proportions, and to evaluate the effect of these proteins on the breads from their physical characteristics. The gluten-free breads were developed according to the 22 factorial design completely randomized to evaluate the effect of isolated zein with the dosage level ranging from 0 to 8% and hydrolyzed collagen ranging from 0 to 4%, totaling 4 treatments (Control, Collagen, Zein and Collagen with Zein) with 3 replications each. The treatments were submitted to physical analyses (color, specific volume, bake loss and firmness), which underwent analysis of variance (ANOVA) and Tukey test (p≤0.05) using the Software Statistical Analysis System (SAS®) Studio, and digital microscopy. According to the results, the color of the crust and crumb in the breads had the influence of zein and corn pigments making them yellowish breads. The addition of hydrolyzed collagen and isolated zein had an influence on the specific volume, bake loss and firmness, making the breads with higher specific volume (2,19±0,05 cm3 /g), lower percentage of weight loss (10,16±0,02%) and lower firmness of the crust (5668 gf) compared to the control. Digital microscopy visually proved the increase in crust porosity and the number of crumb cells in protein added breads, making them less firm. Therefore, the addition of zein and hydrolyzed collagen had a positive effect on gluten-free breads in relation to the physical characteristics analyzed.